ANALYSIS OF ARABIC TEACHING BOOKS OF MA CLASS XI 2013 CURRICULUM PUBLISHED 2020 RI MINISTRY OF RELIGION - Farida, Fitria Cinta; Achmad Irsyad Assiddiqi; Mokhammad Miftakhul Huda; Faisol Nasar bin Madi (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This study aims to determine the learning of speaking skills in Arabic textbooks for class XI Madrasah Aliyah 2013 curriculum published by the Ministry of Religion and to find out its advantages and disadvantages. This research uses a qualitative approach with library research. Data collection techniques through documentation records in the form of written data related to the speaking material in the textbook. Furthermore, content analysis and drawing conclusions. The textbook meets the standards of a good textbook. The advantages are (1) Teaching material for speaking is in accordance with the learning objectives. (2) the model of speaking practice is in accordance with the theory (3) The subject matter is factual and real. (4) The instructions used are in accordance with the type of practice. (5) The type of font and size used are appropriate (6) The images presented are suitable, clear and colorful (7) Arabic language skills are separated (8) There is qoimatul mufrodat (9) Mufrodat is arranged based on chapters (10) Presentation of sub-chapters/components very consistent (11) there is a concept map (12) There is a summary at the end of each chapter, (13) The reading material is very attractive and interesting, (14) according to the age and abilities of students (15) the form of training is in accordance with the competence to be measured. While the drawbacks are (1) There are errors in writing book pages, (2) Some of the vowels are incomplete, (3) The preparation of qaimatul mufrodat does not follow the alphabet. (4) there are several blank pages.